Nothing personal, it’s the organization! Links between organizational culture, workplace bullying, and affective commitment - Galanaki, Eleanna; Papalexandris, Nancy; Zografou, Irene; Pahos, Nikolaos (Frontiers in Psychology, 2024)
Extensive attention in organizational research has been dedicated to workplace bullying, primarily focusing on its frequency and impact on both the victim and the bully, emphasizing interpersonal dynamics. This study extends current research by shifting the focus to the organizational level, examining the relationship between organizational culture and affective commitment, mediated by workplace bullying. Utilizing data from two surveys (N=650 in 2012 and N=553 in 2017), the study reveals that dimensions of organizational culture, such as assertiveness, performance orientation, and ingroup collectivism significantly influence workrelated workplace bullying. Performance orientation and assertiveness are positively associated with increased bullying, whereas ingroup collectivism serves as a deterrent. In turn, workrelated bullying negatively impacts affective commitment, while a culture characterized by high ingroup collectivism not only links negatively with bullying but also links positively with affective commitment. This work is one of the first studies to investigate the interplay among several dimensions of organizational culture, workplace bullying, and affective commitment, underscoring the importance of supportive organizational cultures in fostering healthy work environments.